Internet censorship detected in Uganda (Uganda) - Voidly (2026)
CRITICAL severity censorship detected in Uganda. Confidence: 65%. Data sourced from CensoredPlanet.
Censorship Incident ID: UG-2026-0047
Keywords: censorship; UG; censorship; critical